Multilevel analysis of early initiation of breastfeeding in Ethiopia - Hussen, Nuru Mohammed; Kassa, Tigabu Hailu; Habtie, Getnet Mamo (Frontiers in Public Health, 2024)
Introduction Breast milk is the ideal food for the infant and is associated with various public health benefits for both the infant and the mother. The recommended time for early initiation of breastfeeding is within one hour after birth. The prevalence of early initiation of breastfeeding was lower than the plan of the Ethiopian Ministry of Health Sector Development program. Thus, the main objective of this study was to identify individual and group-level factors associated with the early initiation of breastfeeding in Ethiopia. Methods Secondary data on children was obtained from the 2019 Ethiopia mini-demographic and health survey. The survey was a population-based cross-sectional study and was downloaded from the Measure Demographic and Health Survey website (http://www.measuredhs.com). The study included a random sample of 2125 last-born infants who were born within 24 months before the survey. A multilevel binary logistic regression analysis was employed to identify the factors associated with the early initiation of breastfeeding in Ethiopia. Statistical data was analyzed using the Statistical Analysis System (SAS 9.4). Results The prevalence of early breastfeeding initiation was 72%. The higher preceding birth interval (AOR = 1.18, 95% CI: 1.1076, 1.5451), the higher gestational age of infants (AOR = 1.38, 95% CI: 1.2796, 1.4782), the higher number of antenatal care visits (AOR = 1.26, 95% CI: 1.2340, 1.2934), delivery at a health facility (AOR = 1.60, 95% CI: 1.4585, 1.7515), vaginal delivery (AOR = 1.11, 95% CI: 1.1019, 1.1123), mothers with primary education (AOR = 1.14, 95% CI: 1.0204, 1.2738), mothers with secondary education (AOR = 1.54, 95% CI: 1.4678, 1.6190), and mothers with higher education (AOR = 2.62, 95% CI: 2.2574, 3.0526) were associated with higher odds of early initiation of breastfeeding. Being a rural dweller (AOR = 0.63, 95% CI: 0.5684, 0.7038) and the age of mothers (AOR = 0.44, 95% CI: 0.3921, 0.4894) were associated with lower odds of early initiation of breastfeeding. Conclusion Since the prevalence of early initiation of breastfeeding was minimal among rural mothers who delivered their child by caesarean section, this study strongly suggests special supportive care for these mothers.